The Factors Related To Complaints Of Contact Dermatitis On Fish Traders In The Toss 3000 Traditional Market, Batam City - Oktarizal, Hengky; Pitaloka, Rolla; Windusari, Yuanita; Misnaniarti, Misnaniarti; lionardo, Andries; Affandi, Ashar Kholik (Universitas Muhammadiyah Kalimantan Timur, 2022)
Abstract: The skin is the largest external organ of the human body that covers all surfaces of the body. The low level of personal hygiene and lack of attention to the use of clean water for fish traders make it easy for fish traders to get diseases, namely water-borne diseases, one of which is skin disease and others. The purpose of this study was to determine the factors associated with complaints of contact dermatitis among fish traders at the Toss 3000 Traditional Market, Batam City in 2021. This type of research uses an analytic survey, with a cross-sectional study design, this study was conducted to determine the factors of contact dermatitis complaints in fish traders based on the availability of clean water by measuring water pH and personal hygiene. The sample in this study were fish traders in the traditional market toss 3000 Batam City with a total of 62 respondents. The sampling technique in this study was Total Sampling and statistical analysis using the Chi-Square test. The results of the Chi Square test analysis showed that there was a relationship between water pH, Clean Water Availability, and Personal Hygiene on fish traders at Toss 3000 Traditional Market Batam City (p-value <0.05). The description of the availability of clean water for fish traders at the Toss 3000 Traditional Market, Batam City in 2021, namely 13 samples (21%) available clean water and 49 samples (79%). There is a relationship between the availability of clean water and complaints of contact dermatitis among fish traders at the Toss 3000 Traditional Market, Batam City in 2021 with a P value of 0.050 <0.05. For traders, pay attention to the availability of clean water in their respective kiosks, by distinguishing between clean water for personal use and fish cleaning purposes. Keywords: Water pH, Clean Water Availability and Personal Hygiene